Rašytinio paveldo apsauga ir sklaida Lietuvos mokslų akademijos bibliotekoje - (:unkn) unknown (My University, 2009)
The article was prepared on the basis of the report given at the conference „Written Heritage in Scientific Libraries: Traditions and Innovations in Dissemination" (Vilnius; Kaunas, October 17-18, 2006). The article presents an overview of the work done for the preservation and popularization of the written heritage in the Library of the Lithuanian Academy of Sciences during the past five years and considers the issue of connection between the preservation and dispersion of the heritage. The preservation of the written heritage is implemented by the Documents Conservation and Restoration Department, closely collaborating with the Departments of Manuscripts, Rare Books and Old Periodicals. Information technologies specialists frequently provide assistance. The preservation of the documents is ascertained by their restoration and conservation accompanied by a scientific analysis. Another important way to preserve and disseminate the documents is to digitalize them. Traditional methods of publicizing the heritage: creation of electronic catalogue, compilation of printed bibliographic publications, publication of the documents, mounting exhibitions - are also not forgotten.
Preservation and dissemination of the written heritage in the Library of the Lithuanian academy of sciences
Skyriaus antraštė: Darbo aktualijos